The Cambridge handbook of systemic functional linguistics - Bowcher, Wendy L.; Fontaine, Lise; Schonthal, David; Thompson, Geoff , 1947- (Cambridge handbooks in language and linguistics, 2019)
"Presenting a field-defining overview of one of the most appliable linguistic theories available today, this handbook surveys the key issues in the study of Systemic Functional Linguistics (SFL), covering an impressive range of theoretical perspectives. Written by some of the world's foremost SFL scholars, including M.A.K. Halliday, the founder of SFL theory, the handbook covers topics ranging from the theory behind the model, discourse analysis within SFL, applied SFL, to SFL in relation to other subfields of linguistics such as intonation, typology, clinical linguistics and education. Chapters include discussion on the possible future directions in which research might be conducted and issues that can be further investigated and resolved. Readers will be inspired to pursue the challenges raised within the volume, both theoretically and practically"-- Provided by publishe